Symbiotic strategies: deciphering the role of gut microbiota in the nutrition and metabolism of fish and shellfish - Rai, Nandini; Kachore, Ankit; Julka, J. M.; Panigrahi, Akshaya; Das, Sofia Priyadarsani; Nan, Fan-Hua (Frontiers in Cellular and Infection Microbiology, 2025)
The gastrointestinal microbiota is crucial for the health and physiology of aquatic organisms, influencing their nutrition, metabolism, and immune responses. This review compares the diversity and function of gut microbial communities in finfish and shellfish, highlighting differences between freshwater and marine species as well as variations within shellfish taxa. We examine how these microbes aid in digesting complex dietary substrates, assimilating nutrients, and synthesizing essential metabolites, all of which are vital for host health. The structure of these microbial communities is shaped by a complex interplay of environmental factors, such as water temperature, salinity, and pH, and host-specific factors, including genetics and diet. A comprehensive understanding of these interactions is key to improving gut health and nutrient use in aquaculture. This review also identifies future research directions, focusing on the use of probiotics, prebiotics, and dietary interventions. These strategies, combined with multi-omics approaches, have great potential to enhance the sustainability of aquaculture by improving growth performance, feed conversion efficiency, and disease resistance in farmed aquatic species.